1996
DOI: 10.1095/biolreprod54.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Endometrium Synthesizes and Releases Platelet-Activating Factor, Which Can Cause the Release of Prostaglandin F2α by the Uterus in Situ1

Abstract: Explanted endometrial tissue from ovariectomized ewes that had received hormone replacement to mimic the luteal phase released platelet-activating factor (PAF) into medium in vitro. On Day 14, 310.1 (261-2185), and on Day 15, 424.4 (14.1-590.7) pg PAF (median 25th-75th percentile; p > 0.05) was released per 100 mg endometrial tissue after a 20-min incubation. A regulatory and final enzyme in the PAF biosynthetic pathway, lysoPAF:acetyltransferase, was also present with a specific activity of 0.533 +/- 0.124 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…E 2 amplified the stimulatory effects of P 4 and oxytocin on endometrial PGF 2␣ synthesis, whereas E 2 alone had no effect on PGF 2␣ secretion by bovine endometrial tissue in short-term culture (46). E 2 stimulated both basal and oxytocin-regulated PGF 2␣ secretion in ovariectomized P 4 -primed cows (6). These data have demonstrated that E 2 did not stimulate PGF 2␣ release by bovine endometrium without P 4 pretreatment.…”
Section: Discussionmentioning
confidence: 67%
“…E 2 amplified the stimulatory effects of P 4 and oxytocin on endometrial PGF 2␣ synthesis, whereas E 2 alone had no effect on PGF 2␣ secretion by bovine endometrial tissue in short-term culture (46). E 2 stimulated both basal and oxytocin-regulated PGF 2␣ secretion in ovariectomized P 4 -primed cows (6). These data have demonstrated that E 2 did not stimulate PGF 2␣ release by bovine endometrium without P 4 pretreatment.…”
Section: Discussionmentioning
confidence: 67%
“…Ewes were allowed to recover for Ն6 wk before treatment began. Hormone replacement of ovariectomized ewes with progesterone and estradiol-17␤ (Sigma Chemical, St. Louis, MO) was as previously described (2,4,11). This hormone regimen creates blood hormone levels similar to those achieved in the natural estrous cycle (11).…”
Section: Methodsmentioning
confidence: 99%
“…This 15-keto derivative is stable (26). Thus PGF2␣ release is conventionally assessed by measurement of PGFM in peripheral blood (2,4). The PGFM assay used was as previously described (4), and the assay sensitivity was 0.05 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is also produced by a number of nonimmune cells such as endothelial (9), vascular, muscle (43), glomerular (13) and endometrial cells (4,5,7,45). PAF plays a role in many reproductive events (16), including ovulation (1), fertilization (27), implantation and early development of embryo (28).…”
Section: Introductionmentioning
confidence: 99%